Integration of Geographical Information System and Multi Criteria Evaluation for Identification of Suitable Urban School Sites - Bukhari, Zubaidah (2010)
Schools which are located in a strategic, healthy and safe area play an important role in improving students’ performance and excellence. To ensure both success and long-term sustainability of the school planning, the finding of suitable sites for school is important and challenging. This study delves into a systematic site selection process to establish a new primary public school. It was carried out through the use of Geographic Information System (GIS) and multi criteria evaluation model (MCE). Decision makers’ evaluation and community opinions have been used for developing a set of school siting criteria and school planning data model which were used to design a number of potential sites by using the spatial analysis model. Mukim Batu which is located in the Federal Territory of Kuala Lumpur (WPKL) had been selected as the study area. The demography analysis identified 18.1% of the study area is in rapid growth while the safety analysis identified 17.3% of the area is in a safe zone. Constraint analysis identified 5% of the study area is suitable for school development. Weighted Linear Combination (WLC) technique had been used to combine the 3 analyses namely demographic, safety and constraint analysis to identify 6 potential sites. The accessibility analysis was used to further analyze the potential sites by using community opinions. The potential sites were compared with the field validation data and it was found to be reliable. This study has improved the school planning guideline and has brought a new approach for school site selections which combine the decision makers and community needs in the school site selection on the decision making process.